The Effect of Perceived Ease of Use and Perceived Usefulness on Intention to Use Mobile Banking Apps - Andriya Risdwiyanto; Bambang Irjanto (Westscience Press, 2026)
This study examines the influence of perceived ease of use (PEOU) and perceived usefulness (PU) on the intention to use mobile banking apps in Indonesia. A total of 175 participants were surveyed, and the data were analyzed using SPSS version 25. The results indicate that both PEOU and PU significantly affect users' intention to use mobile banking apps, with perceived usefulness showing the strongest influence. Perceived ease of use also plays a significant role, though to a lesser extent. The findings suggest that enhancing both the usability and usefulness of mobile banking apps can drive higher adoption rates. This study contributes valuable insights for mobile banking developers and financial institutions aiming to improve user engagement and increase mobile banking adoption in Indonesia.